Arousal Predisposition as a Vulnerability Indicator for Psychosis: A General Population Online Stress Induction Study. (23rd June 2015) - Clamor, Annika; Warmuth, A. Malika; Lincoln, Tania M.
Abstract : Explanatory models ascribe to arousability a central role for the development of psychotic symptoms. Thus, a disposition to hyperarousal (i.e., increased arousal predisposition (AP)) may serve as an underlying vulnerability indicator for psychosis by interacting with stressors to cause symptoms. In this case, AP, stress-response, and psychotic symptoms should be linked before the development of a diagnosable psychotic disorder. We conducted a cross-sectional online study in a population sample (N = 104 ;M age = 27.7 years, S D = 11.2, range 18–70). Participants rated their AP and subclinical psychotic symptoms. Participants reported their stress-levels before and after two stress inductions including an arithmetic and a social stressor. The participants with an increased AP generally felt more stressed. However, AP was not associated with the specific stress-response. As expected, positive psychotic symptoms were significantly associated with AP, but this was not mediated by general stress-levels. Its association to subtle, nonclinical psychotic symptoms supports our assumption that AP could be a vulnerability indicator for psychosis. The trait is easily accessible via a short self-report and could facilitate the identification of people at risk and be a promising target for early stress-management. Further research is needed to clarify its predictive value for stress-responses.